2012
DOI: 10.1007/s12013-012-9427-1
|View full text |Cite
|
Sign up to set email alerts
|

Association with Leptin Gene c.-2548 G>A Polymorphism, Serum Leptin Levels, and Body Mass Index in Turkish Obese Patients

Abstract: Leptin is a protein hormone which plays a critical role in the regulation of both body-weight through reducing food intake and stimulating energy expenditure. Several polymorphisms in leptin gene (LEP), which encodes for leptin, have been described. However, its association with obesity is still controversial. Therefore, in the present study, we aimed to investigate whether LEP c.-2548 G>A polymorphism was associated with serum leptin levels, lipid parameters, and body mass index in Turkish obese patients. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 22 publications
4
37
1
Order By: Relevance
“…The detailed characteristics of these studies are shown in table 1. In 9 articles published between 2006 and 2012, 1,372 obese subjects and 1,616 controls were involved from a wide range of regions including Europe [19,21,22,27], South America [18,23,25] and North Africa [24,26]. Of the selected studies, 6 related to a Caucasian population and 3 to a South American population (mixed race).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed characteristics of these studies are shown in table 1. In 9 articles published between 2006 and 2012, 1,372 obese subjects and 1,616 controls were involved from a wide range of regions including Europe [19,21,22,27], South America [18,23,25] and North Africa [24,26]. Of the selected studies, 6 related to a Caucasian population and 3 to a South American population (mixed race).…”
Section: Resultsmentioning
confidence: 99%
“…Of the selected studies, 6 related to a Caucasian population and 3 to a South American population (mixed race). There were 2 studies in which the genotypes in the control group were not in HWE [26,27]. Two studies were performed by the same investigator [23,25], and it is not clear whether different individuals were genotyped or whether some individuals were counted twice (the author rejected our inquiry e-mail).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LEP gene, human homologue of the rat obese gene cloned and sequenced by Zhang et al (1994), is located on autosome 7 (7q31.3) and the length of its mRNA in adipose tissue is 4.5 kb (Mohammadzadeh et al, 2015). There are several studies indicating the significant association between polymorphisms in LEP gene and obesity (Duarte et al, 2006), hypertension (Mendoza-Núñez et al, 2006), coronary artery diseases and metabolic syndrome (Kim et al, 2008), insulin resistance (Chiu et al, 2004), type 2 diabetes mellitus (Han et al, 2008) and cancer (Mohammadzadeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies indicating the significant association between polymorphisms in LEP gene and obesity (Duarte et al, 2006), hypertension (Mendoza-Núñez et al, 2006), coronary artery diseases and metabolic syndrome (Kim et al, 2008), insulin resistance (Chiu et al, 2004), type 2 diabetes mellitus (Han et al, 2008) and cancer (Mohammadzadeh et al, 2015). The G2548A polymorphism (rs7799039: guanine > adenine) are studied widely because it has been associated with leptin production and secretion (Suriyaprom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%